Pola Kejadian Malaria Pada Tenaga Kerja Di Area Lowland PT Freeport Indonesia - Zaman, Mokhamad Muniru; Martini, Martini; Fauzi, Muh; Udijono, Ari (Jurnal Riset Kesehatan Masyarakat, 2024)
Malaria is caused by the plasmodium parasite and is transmitted through the bite of an infected female Anopheles mosquito. Plasmodium falciparum and plasmodium vivax are the most common types of plasmodium in Indonesia. Plasmodium malariae is found in several regions, such as Lampung and Papua, and plasmodium ovale is found in the eastern and northern regions of North Sumatra. The aim of this research is to determine the pattern of malaria incidence among workers in the lowland areas of PT Freeport Indonesia. The research method is descriptive observation, by collecting data through interviews and questionnaires. The results of research in the lowland areas of PTFI found that 160 people (91.1%) had a history of malaria, they were exposed to malaria during PTFI, namely low frequency (1-3 times) 76 people (47.5%) and high frequency (4-7 times) 84 people (53.5%). Infection by plasmodium vivax was 133 people (52.6%), plasmodium falciparum 111 people (43.9%), plasmodium ovale 7 people (2.8%), plasmodium malariae 2 people (0.8%). However, most people with a history of malaria, at PT Freeport Indonesia, had the highest frequency (4-7 times) and the highest number of infections by plasmodium was plasmodium vivax.